Highlights of Pancreatobiliary Endoscopy in International Digestive Endoscopy Network 2012: How Much Has It Advanced? - Dong, Seok Ho (The Korean Society of Gastrointestinal Endoscopy, 2012)
The pancreatobiliary organ is composed of one of the most complicated structures and complex physiological functions among other digestive organs in our body. This is why endoscopic procedure in pancreaticobiliary system requires rather complicated techniques. In International Digestive Endoscopy Network (IDEN) 2012, many interesting pancreatobiliay endoscopy related topics were presented. Basic procedures like endoscopic papillary balloon dilation (EPBD), advanced techniques like endoscopic necrosectomy, prevention and management of post-ERCP pancreatitis, and spyglass system are reviewed in this highlight summary.